Pengaruh Current Ratio, Debt to Assets Ratio, dan Total Asset Turn OverTerhadap Return On Asset Pada PT. ACE Hardware Indonesia Tbk Tahun 2014-2021 - Siregar, Siti Aisyah (Lembaga Riset Ilmiah, 2022)
The financial condition of a company is of course very necessary for various parties in need, including for potential investors and creditors and owners to ensure what the sustainability of the company is currently and in the future.To analyze can be done by doing a ratio of liquidity, solvability, activity, and profitability.The purpose of this study is to analyze and find out the influence of Current Ratio, Debt to Asset Ratio, and Total Asset Turn Over on Return On Assets at PT ACE Hardware Indonesia Tbk for the year 2014-2021.This research is an associative study with secondary data obtained from quarterly financial statements for 8 years.The analysis technique carried out is using Multiple Linear Analysis with the help of SPSS data processing.The results of the study said that partially the Current Ratio has no effect on Return On Assets, Debt to Asset Ratio has a negative and significant effect on Return On Assets, Total Asset Turn Over has a positive and significant effect on Return On Assets. While simultaneously Current Ratio, Debt to Asset Ratio, and Total Asset Turn Over have a positive and significant effect on Return On Assets in PT. ACE Hardware Indonesia Tbk 2014-2021. Keyword : Current Ratio; Debt to Asset Ratio; Total Asset Turn Over; Return On Asset